Neurofilament light chain levels in ventricular cerebrospinal fluid after acute aneurysmal subarachnoid haemorrhage. Issue 2 (22nd June 2010) - Zanier, E R; Refai, D; Zipfel, G J; Zoerle, T; Longhi, L; Esparza, T J; Spinner, M L; Bateman, R J; Brody, D L; Stocchetti, N
Abstract : Purpose: The contribution of axonal injury to brain damage after aneurysmal subarachnoid haemorrhage (aSAH) is unknown. Neurofilament light chain (NF-L), a component of the axonal cytoskeleton, has been shown to be elevated in the cerebrospinal fluid of patients with many types of axonal injury. We hypothesised that patients with aSAH would have elevated cerebrospinal fluid (CSF) NF-L levels and sought to explore the clinical correlates of CSF NF-L dynamics. Methods: Serial ventricular CSF (vCSF) samples were collected from 35 patients with aSAH for up to 15 days. vCSF NF-L measurements were determined by enzyme-linked immunosorbent assay. NF-L levels were analysed in relation to acute clinical status, radiological findings and 6-month outcomes. Results: vCSF NF-L concentrations were elevated in all patients with aSAH. Patients with early cerebral ischaemia (ECI), defined as a CT hypodense lesion visible within the first 3 days, had higher acute vCSF NF-L levels than patients without ECI. These elevated NF-L levels were similar in patients with ECI associated with intracranial haemorrhage and ECI associated with surgical/endovascular complications. vCSF NF-L levels did not differ as a function of acute clinical status, clinical vasospasm, delayed cerebral ischaemia or 6-month Glasgow Outcome Scale. Conclusions: Elevated vCSF NF-L levels may in part reflect increased injury to axons associated with ECI. However, our results suggest that axonal injury after aSAH as reflected by release of NF-L into the CSF may not play a major role in either secondary adverse events or long-term clinical outcomes.